Biomarkers for primary open-angle glaucoma progression. (June 2022) - Zhao, Mengya; Ma, Ping; Xie, Qinghong; Bui, Anh D.; Yonamine, Sean; Hinterwirth, Armin; Zhong, Lina; Chen, Cindi; Doan, Thuy; Han, Ying
Abstract: Glaucoma is a heterogeneous group of progressive optic neurodegenerative. Although most patients with primary open angle glaucoma (POAG) are stable for many years, certain subgroups of POAG patients could progress over time even with treatment. This study is to identify aqueous humor (AH) biomarkers that may be associated with disease progression in POAG patients. Gene differential expression study of prospectively collected AH from patients with stable or progressive POAG. Metagenomic deep sequencing (MDS) was performed on the aqueous fluid of 20 patients with stable POAG and 20 patients with progressive POAG. Differential gene expression analysis was performed to identify host transcriptome signatures. A total of 21 transcripts were differentially expressed between groups. Differential transcripts identified by MDS. Twenty transcripts were up-regulated and 1 transcript was down-regulated in progressive POAG patients compared to stable patients. Of those, 11 transcripts were eye-related, and 5 transcripts were related to glaucomatous phenotypes (Fibronectin type III domain containing 3B (FNDC3B), Clusterin (CLU), Proprotein convertase subtilisin/kexin type 6 (PCSK6), Cadherin EGF LAG seven-pass G-type receptor 1 (Celsr1), and Rho guanine nucleotide exchange factor 4 (ARHGEF4)). Biomarkers associated with POAG progression can be identified from aqueous fluid. Identification of the biomarkers may improve glaucoma surveillance for progressive POAG. Highlights: Identify biomarkers associated with POAG progression from aqueous samples. Differential transcripts identified by MDS. Improve glaucoma surveillance for progressive POAG.